The strongest correlates of PTSD for firefighters: number, recency, frequency, or perceived threat of traumatic events? - Pinto, Ricardo José (2015)
Firefighters experience a wide range of traumatic events while on duty and are at risk to develop psychopathology and posttraumatic stress disorder (PTSD). According to cognitive models, the person's interpretation of the traumatic event is responsible for the development of PTSD rather than the traumatic event itself. This cross-sectional study aimed to explore the contribution of perceived threat to explain PTSD symptoms in Portuguese firefighters, after adjusting for potential confounding factors. A sample of 397 firefighters completed self-report measures of exposure to traumatic events, psychopathology, and PTSD. Perceived threat explained unique variance in PTSD symptoms, R-2 = .40, Delta R-2 = .02, F(10, 367) = 24.55, p < .001, Cohen's f(2) = .03, after adjusting for psychopathology, number, recency, and frequency of the events, and other potential confounding variables. The association between psychopathology and PTSD was also moderated by perceived threat, R-2 = .43, Delta R-2 = .03, F(11, 366) = 25.33, p < .001, Cohen's f(2) = .05. Firefighters may benefit from interventions that focus on perceived threat to prevent PTSD symptoms.